Aplicação da metodologia Euleriana-Lagrangiana à análise do processo de separação em ciclones - Salvo, Ricardo de Vasconcelos (2013)
In this work, first is presented an introduction to the simulation of two-phase flows, followed by a small motivational text, where the importance of cyclone separators in petrochemical units, more specifically in catalytic cracking units, is shortly addressed. In sequence the state of the art in the simulation of gas-solid flow within cyclones is evidenced by a bibliographic review, which also address the use of Eulerian-Eulerian and Eulerian- Lagrangiam methods, which are the main approaches in the simulation of multi-phase flows. Next, the numerical schemes used for the discretization of the continuous phase equations and, in a detailed manner, the numerical schemes used for the discretization of the dispersed phase equations are shown. The study of the mono-phase flow in two different cyclones, a cylindrical one without the underflow duct and another one with a dust bin attached, is discussed and some qualities of the used methodology are presented, highlighting that in this initial study the simulated flows cover an operating range, as a function of the Reynolds number based on the cyclone inlet velocity, from 15,000 to 522,000. Then a study concerning the influence of the temporal dicretization schemes and sub-time steps for such integration, in the grade efficiency of a small laboratory cyclone is presented, the turbulence modeling and the computational mesh (regarding number and distribution of the elements), effects are also addressed. Further, a study on the effects of the overflow duct shape on the cyclone grade efficiency presented. Finally a 0.4 m diameter cyclone operating at Reynolds number of approximately is simulated, the average and RMS axial and tangential velocity profiles, as well as the grade efficiency are compared to experimental data available in the literature, showing in a clear manner the applicability of the chosen methodology.